Characterization of flavonoids in Millettia nitida var. hirsutissima by HPLC/DAD/ESI-MSn - Min Ye; Wen-Zhi Yang; Ke-Di Liu; Xue Qiao; Bei-Jia Li; Jun Cheng; Jie Feng; De-An Guo; Yu-Ying Zhao (Elsevier, 2012)
Millettia nitida var. hirsutissima is a Chinese herbal medicine used for the treatment of gynecological diseases. An HPLC/DAD/ESI-MSn method was established for the rapid separation and characterization of bioactive flavonoids in M. nitida var. hirsutissima. A total of 32 flavonoids were detected, of which 14 compounds were unambiguously characterized by comparing their retention time, UV, and MS spectra with those of the reference standards, and the others were tentatively identified based on their tandem mass spectrometry fragmentation data obtained in the negative ionization mode on line. Nineteen of these compounds characterized were reported from this plant for the first time. Keywords: HPLC/DAD/ESI-MSn, Millettia nitida var. hirsutissima, Mass spectrometry, Flavonoids